2014
DOI: 10.1097/sla.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

Early Complications After Laparoscopic Gastric Bypass Surgery

Abstract: Intraoperative adverse events and conversion to open surgery are the strongest risk factors for serious complications after laparoscopic gastric bypass surgery. Annual operative volume and total institutional experience are important for the outcome. Patient related factors, in particular age, also increased the risk but to a lesser extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(50 citation statements)
references
References 24 publications
4
44
1
1
Order By: Relevance
“…Patients in the FT group were on average a few years older. Previous research has shown that patient with a higher age have an increased risk at postoperative complications [18]. Nonetheless, age turned out not to be a significant predictor after univariate analysis on postoperative complications in the current study.…”
Section: Discussioncontrasting
confidence: 70%
“…Patients in the FT group were on average a few years older. Previous research has shown that patient with a higher age have an increased risk at postoperative complications [18]. Nonetheless, age turned out not to be a significant predictor after univariate analysis on postoperative complications in the current study.…”
Section: Discussioncontrasting
confidence: 70%
“…More women than men undergo laparoscopic gastric bypass surgery [22], and it is thus important to see if the increased risk for postoperative pain amongst women previously described [5] is, in fact, gender-associated or if there is another explanation. Even though further studies are needed to more fully clarify this matter, the results of the present study indicate that factors other than gender alone are of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality related to bariatric surgeries remains below 1% and is approximately 0.3% in international studies. (9-11) Among early complications, the most important include surgical wound infections, anastomosis dehiscence, fistulas, bleeding, venous thromboembolism and incisional hernias. The prevalence of postoperative complications is low, including bleeding in 0.5%, thromboembolism in 0.8% and operative wound complications in 1.8% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of postoperative complications is low, including bleeding in 0.5%, thromboembolism in 0.8% and operative wound complications in 1.8% of cases. (9-11) …”
Section: Introductionmentioning
confidence: 99%